CULTURE AND LANGUAGE INFLUENCE UPON TRANSLATION IN THE CONTEXT OF INTERCULTURAL COMMUNICATION - Oksana Biletska (Культура і мистецтво у сучасному світі, 2017)
The purpose of the article is to investigate the cultural and linguistic condition of the translation of text material in the context of intercultural communication. This, in turn, is because the translation is a kind of creative activity and is a subject to the rules of linguistics and cultural studies. Each language is unique. The language model of the world is determined by the cultural characteristics, that is ethnic, social peculiarities and norms, as well as through the economic achievements of the nation at a certain stage of its development. Cultural studies are an integral part of the linguistic model, and some scholars tend to think that in reality we translate not language but culture [8, p. 155]. The research methodology consists in using such research methods as studying, analyzing and generalizing in order to open the assumption about the similarity of languages to a closed system, asserting that the culture of the people and its language are interconnected and tend to influence each other. Besides, a special turn in the life of society associated with the processes of integration, globalization, the growth of the importance of intercultural, relationships, has determined the deep interpenetration of functional, pragmatic, language and culture studies and translational researches. The scientific novelty of the work is to expand the representation of the culture relationship, which usually leads to the parallelism of the content, greatly facilitating the process of adaptation in comparison with those cases where cultures do not have points of contact at all. Since there are no cultures in which the same signs (linguistic and non-verbal) would create similar meanings and would be organized in the same way, it is not possible to speak of the absolute correspondence of the adaptation of the original message and the translated message culture elements. Conclusions. Culture determines the space beyond which it is impossible to come up with the adaptation of translation texts for various languages and cultures, in which language as a sign system of culture is most often used for the transmission of messages. In the process of adaptation, it is first of all considered necessary to establish whether it is possible to replace the element of culture used in the original message with the corresponding equivalent, or the given symbol can be translated into the translation culture only by means of verbal means. Language consists not only of the values of symbols; it is based on a cultural code that functions in order to perform certain communicative tasks.